2015
DOI: 10.3998/ergo.12405314.0002.014
|View full text |Cite
|
Sign up to set email alerts
|

Why Is There Female Under-Representation among Philosophy Majors?

Abstract: Why does female under-representation emerge during undergraduate education? at the University of Sydney, we surveyed students before and after their first philosophy course. We failed to find any evidence that this course disproportionately discouraged female students from continuing in philosophy relative to male students. instead, we found evidence of an interaction effect between gender and existing attitudes about philosophy coming into tertiary education that appears at least partially responsible for thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 32 publications
0
37
0
1
Order By: Relevance
“…Evidence suggests that women are less comfortable than men speaking in class, including expressing their opinions and asking or answering questions, and that this difference partially accounted for the relationship between gender of respondent and their willingness to take more philosophy (Thompson et al, ). A study in Australia found that on the first day of an introductory philosophy course, women were less inclined to predict that they would be comfortable contributing to class discussion (Baron, Dougherty, & Miller, ). Finally, in New Zealand, women reported feeling less comfortable expressing their opinions and asking or answering questions in tutorials compared to men (Brock et al, ).…”
Section: Potential Factorsmentioning
confidence: 99%
“…Evidence suggests that women are less comfortable than men speaking in class, including expressing their opinions and asking or answering questions, and that this difference partially accounted for the relationship between gender of respondent and their willingness to take more philosophy (Thompson et al, ). A study in Australia found that on the first day of an introductory philosophy course, women were less inclined to predict that they would be comfortable contributing to class discussion (Baron, Dougherty, & Miller, ). Finally, in New Zealand, women reported feeling less comfortable expressing their opinions and asking or answering questions in tutorials compared to men (Brock et al, ).…”
Section: Potential Factorsmentioning
confidence: 99%
“…The assumption that her aversion to conflict is the reason a woman does not stay in philosophy is thoroughly unsubstantiated—and it appears to be at odds with reality. A study conducted in Sydney found no evidence that either the hostile‐climate or the aggressive‐argumentation hypothesis for philosophy was grounded in fact (Baron, Dougherty, and Miller ). Female students were not significantly more uncomfortable in the classroom at the beginning of a semester than their male counterparts, and they did not become more so over time.…”
Section: Sorting Fact From Fiction: Philosophical Intuitions and Diffmentioning
confidence: 99%
“…By acknowledging the presence of such biases, we may counteract their potentially harmful consequences and encourage more women to stay on in philosophy. Research demonstrates that female students reported being less confident in their philosophical ability and less able to see themselves as philosophers (Baron, Dougherty, and Miller ). One of the most obvious and straightforward explanations of why women might not be drawn to disciplines like philosophy in the same numbers as men is simply that you can’t be what you can’t see (attributed to Marian Wright Edelman ).…”
Section: How To Increase Minority Representation?mentioning
confidence: 99%
See 1 more Smart Citation
“…However, this research is even more controversial than IAT tasks [78,79], and the experimental studies beginning to trickle out [80][81][82][83] offer little to no evidence of climate issues in introductory philosophy courses where the "the only statistically significant" decline in women's participation occurs (from 43% in introductory courses to 35% of majors) [80] (p. 2). Thompson et al [80] asked introductory classes over fifty climate-related questions (let us note what questions and answers ought to count as pertaining to climate-related bias is not obvious) and their results led them to propose that philosophers should consider changing their course methods and content to better fit women's preferences, such as by deemphasizing thought experiments [80] (pp.…”
Section: Stereotype Threat and Curriculum Inclusivitymentioning
confidence: 99%